Pedagogical Leadership Based On Religious Character Education At Hidayatullah Integral Elementary School: A Response To The Global Challenges Of The 21st Century - Ade Putra Tri Prima; Rika Azizah; Asbani Asbani; Tomi Hidayat; Adi Asmara (Journal of Research in Social Science and Humanities, 2025)
This study aims to examine the form of Islamic values-based pedagogical leadership implemented at SD Integral Hidayatullah Putri Hijau in addressing the global challenges of the 21st century. These challenges include moral crises, the flow of globalization, technological disruptions, and socio-cultural changes that directly affect the educational landscape. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, field observations, and document analysis. The findings indicate that the principal and teachers at SD Integral Hidayatullah Putri Hijau practice integrative pedagogical leadership by aligning Islamic vision with contextual learning strategies. Core values such as honesty, responsibility, discipline, and Islamic brotherhood serve as the foundation in decision-making processes and educational interactions. Additionally, the integration of spiritual values within the learning process, holistic character development, and the teachers’ role as role models are key elements in nurturing adaptive, critical, and morally upright students. Character-based pedagogical leadership has been proven effective in establishing an educational ecosystem capable of facing contemporary challenges while maintaining Islamic identity. This study further reveals a significant correlation and regression between pedagogical leadership and the development of students’ religious character, as well as their preparedness in confronting the global challenges of the 21st century.